5 Infrared Drying - Gikuru, Mwithiga; Nindo, Caleb (CRC Press, 2010)
This chapter will present the mechanism, techniques, and advantages of infrared (IR) drying  for various food and agricultural products. The propagation of IR radiation from a source  (considered as any material at a temperature above absolute zero Kelvin) to other materials  is discussed, and emphasis is placed on the subsequent transformation of the IR radiation  into thermal energy for the drying of foods. The advantages and disadvantages of IR drying  are briefly reviewed, followed by a discussion of selected applications in the processing of ...